The Efforts of Couples with Blind Disabilities in Realizing the Sakinah Family Perspectives on the Hierarchy of Needs Theory: Case Study of Pertuni Malang Regency - Ritonga, Raja Doli Jaya; Ch, Mufidah; Wahidi, Ahmad; Muhammad, Hasman Zhafiri (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
Marriage is a fundamental right for all citizens, including individuals with visual impairments. It aims to achieve a harmonious, loving, and compassionate (sakinah, mawaddah, rahmah) family life. This study explores the concept of the sakinah family and the efforts to realize it from the perspective of visually impaired couples in Pertuni Malang Regency, using Maslow's hierarchy of needs theory. Employing a qualitative approach and empirical legal research, the study identifies six key components of a sakinah family: reciprocation, harmony, gratitude, community contribution, independence, and nurturing beloved, righteous children. The research reveals that visually impaired couples fulfill their physiological needs by working as therapists, teachers in special education, and Quranic reciters (Qariah). They achieve a sense of security through stable income, savings, frugality, good relations, home ownership, trust in government, and family support. Love and belonging are fostered through spousal attention, children's care, family involvement, community support, and government assistance. Esteem needs are met through community engagement and participation in social activities. Lastly, self-actualization is pursued by passionately working, engaging in organizational activities, participating in community events, and channeling personal hobbies. The findings highlight the resilience and adaptability of visually impaired couples in meeting their needs and building a sakinah family, contributing to their overall well-being and societal inclusion. Perkawinan adalah hak setiap warga negara tidak terkecuali penyandang disabilitas tunanetra. Tujuan perkawinan sebagaimana dijelaskan dalam Kompilasi Hukum Islam adalah mewujudkan kehidupan rumah tangga yang sakinah, mawaddah dan rahmah. Penelitian ini mengeksplorasi konsep keluarga sakinah dan upaya mewujudkannya dari sudut pandang pasangan disabilitas tunanetra di Pertuni Kabupaten Malang dengan menggunakan teori hierarki kebutuhan Maslow. Dengan menggunakan pendekatan kualitatif dan penelitian hukum empiris, penelitian ini mengidentifikasi enam komponen utama keluarga sakinah: Mubadalah atau Kesalingan, keharmonisan, rasa syukur, berkontribusi bagi masyarakat, kemandirian, dan melahirkan keturunan yang sholih dan sholehah. Penelitian ini menunjukkan bahwa upaya Upaya pasangan penyendang disabilitas tunanetra Pertuni Kabupaten Malang dalam membentuk keluarga sakinah perspektif teori hierarki kebutuhan: Pemenuhan kebutuhan fisiologis diupayakan dengan bekerja sebagai terapis, mengajar sebagai Guru di sekolah luar biasa, dan menjadi Qariah. Pemenuhan rasa aman diupayakan dengan memiliki penghasilan, menabung dan berhemat, baik kepada orang lain, memiliki rumah sendiri, percaya kepada pemerintah dan kehadiran keluarga. Pemenuhan rasa cinta diupayakan dengan perhatian pasangan, perhatian anak, perhatian keluarga, perhatian masyarakat sekitar dan perhatian pemerintah. Pemenuhan rasa penghargaan diupayakan dengan dibutuhkan masyarakat, dibantu masyarakat, dan dilibatkan dalam kegiatan masyarakat. Pemenuhan aktualisasi diri yang diupayakan dengan bekerja penuh semangat, terlibat dalam organisasi Pertuni, aktif dalam kegiatan warga dan menyalurkan hobi. Temuan ini menyoroti ketahanan dan kemampuan beradaptasi pasangan tunanetra dalam memenuhi kebutuhan mereka dan membangun keluarga sakinah, sehingga berkontribusi terhadap kesejahteraan dan inklusi sosial mereka secara keseluruhan.